Design-Related Causes of Rework and the Performance of Oil and Gas Projects in Nigeria - Wilson, Jimmy Uso; Odesola, Isaac Abiodun (International Journal of Sustainable Construction Engineering and Technology, 2017)
In recent times, the need to optimize project performance has been on the front burner of International Oil Companies, especially in developing countries. The quest for rework reduction to improve project performance underpins this research. This study assesses the frequency of occurrence of design-related causes of rework and its influence on project performance in terms of cost and time. A survey research design approach was adopted which involved a stratified random sample of 500 contractors and 385 consultants. Data were collected through structured questionnaire and analysed using Mean Item Score, Spearman Rank Correlation test, Kruskal Wallis test and One Sample T-test. The result shows that there is significant correlation between contractors and consultantsâ€™ perceptions of the frequency of occurrence of design-related causes of rework. It also shows that design-related causes of rework have significant influence on project time and cost performance. In addition, the project team members ranked errors and omission in design document, ineffective communication between project team members, design changes, lack of site verification by design team and lack of as-built documentation as the top five frequently occurring design-related causes of rework in oil and gas projects. Furthermore, project location does not influence the frequency of occurrence of design-related causes of rework and its impact on the performance of oil and gas projects. Â It is concluded that there is need for effective design and quality management practices to enhance oil and gas project delivery. It is therefore recommended that construction professional in the oil and gas industry should implement design management surveillance and constructability reviews during the design phase as these are effective strategies to reduce design-related causes of rework which will lead to improved project performance in the oil and gas sector.